Penyuluhan Pembuatan Masker Wajah Antiaging dari Tanaman Bandotan (Ageratum conyzoides) di Kelurahan Cemani - Disa Andriani; Dian Puspitasari (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
Skin aging is a natural process that cannot be avoided, but it can be slowed down through proper skin care. The use of natural face masks is one of the safe, affordable, and relatively non-invasive treatment alternatives without long-term side effects. The bandotan plant (Ageratum conyzoides L.) is a weed that grows wild in the Cemani Village area, Sukoharjo Regency. Although often considered worthless, this plant actually contains active compounds such as flavonoids, tannins, and saponins that have the potential to be antioxidants. Therefore, this service activity aims to provide counseling and training to the people of Cemani Village regarding the manufacture of face masks made from bandotan plants. This program is carried out with several procedural stages, starting from the interpretation of problems on the land, followed by the preparation of the timeline for the implementation of activities, then counseling and ending with a workshop session on the procedure for making antiaging masks for bandotan herbs. The program ended with an assessment of the evaluation of the activities. This activity was attended by 20 participants of the Cemani village PKK mobilization team. Based on the pretest and posttest scores, there was an increase in public knowledge about the program carried out with an average of 80 pretests and an increase in the average percentage of posttest scores up to 95.83. In the assessment of the questionnaire, public satisfaction with the implementation of the activity was classified as very satisfied with a score of 92.67.